Effect of the location pattern of rural residential buildings on natural ventilation in mountainous terrain of central China. (15th March 2022) - Xie, Mingjing; Wang, Yuran; Liu, Zhengxuan; Zhang, Guoqiang
Abstract: The use of natural ventilation in buildings to reduce the energy consumption and CO2 emission has been widely investigated and practiced, but few existing studies have considered the exploration and assessment of natural ventilation in different location patterns of rural residential buildings in the mountainous terrain of China. In this paper, the representative rural residential buildings are firstly selected in Huarong, Pingjiang and Liuyang regions of northern Hunan Province to carry out on-site survey works to determine building types, physical parameters and layout forms. Then, the wind tunnel experiments are carried out to investigate the effectiveness of natural ventilation under different location patterns, and the monitored results are compared with simulated data. The results show that the experiments and simulations are in satisfactory agreement. The experimental data also indicate that when the modelled distance of 120 mm (i.e. 12 m between the building and hilly terrain in practical application) is the best option for building natural ventilation. Based on the investigation and statistical data, the natural ventilation effectiveness under different location patterns and operational conditions is simulated using CFD methods, and it is obtained the most favourable location pattern for natural ventilation. The results show that the winter ventilation of buildings in the existing location pattern is significantly obstructed in the hilly terrain, which is favourable to the indoor thermal environment, however, the natural ventilation is compromised to a certain extent in summer. Furthermore, the findings also show that, regardless of the hilly terrain's height at 50 m or 150 m, the buildings are able to avoid natural ventilation in winter to the maximum extent when the distance between the buildings and the frontier of the hilly terrain is double that of the building height (i.e. 12 m). This study could contribute to theoretical instructions for optimum design of natural ventilation of rural residential buildings in the mountainous terrain of central China.